The PiCT® test is a reliable alternative to the activated partial thromboplastin time in unfractionated heparin therapy management: results from a multicenter study. (19th October 2016) - Brisset, A. C.; Ferrández, A.; Krause, M.; Rathbun, S.; Marlar, R.; Korte, W.
Abstract : Essentials Activated partial thromboplastin time (APTT) or anti‐Xa tests are used to monitor heparin. Prothrombinase‐induced Clotting Time (PiCT) was compared to APTT in a clinical study. PiCT shows higher correlation to anti‐Xa than APTT does and is more comparable between centers. PiCT demonstrates significantly higher accuracy and reliability than APTT in heparin monitoring. Summary: Background: Unfractionated heparin (UFH) is still a commonly used anticoagulant for prevention and treatment of thromboembolism in a variety of situations. Increasingly, chromogenic anti‐Xa assays are used for UFH monitoring given the high variability of the activated partial thromboplastin time (APTT) in this setting. On the other hand, and despite the known variability, the APTT test remains the most frequently used monitoring tool in UFH therapy because of its broad availability, lower costs and wide acceptance. Various guidelines continue to recommend the use of the APTT as an anti‐Xa surrogate, but this approach remains controversial. Objective: To assess the prothrombinase‐induced clotting time (PiCT ® ) test, reported in seconds, as an alternative to the APTT in the management of UFH‐mediated anticoagulation. Methods: Plasma samples from patients receiving UFH were obtained in three different centers in the USA and Europe. Samples were analyzed for PiCT, APTT and anti‐Xa activities with conditions set to allow comparability. Target‐ranges in seconds for PiCT and APTT were established for a UFH concentration of 0.3–0.7 IU mL −1, derived from anti‐Xa results as suggested by the ACCP guidelines. Results: PiCT demonstrated better correlation with anti‐Xa IU mL −1 than APTT, higher ability to identify samples within target range and, importantly, comparable target‐ranges between different centers. Conclusion: Accuracy and reliability of PiCT are significantly better than those of APTT in monitoring UFH for anticoagulant therapy.